2021
DOI: 10.3389/fresc.2021.687554
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Efficacy and Functionality of Ten Commercially Available Wrist-Hand Orthoses in Healthy Females: Wrist Range of Motion and Grip Strength Analysis

Abstract: Objective: Wrist-hand orthoses (WHOs) are prescribed for a range of musculoskeletal/neurological conditions to optimise wrist/hand position at rest and enhance performance by controlling its range of motion (ROM), improving alignment, reducing pain, and optimising grip strength. The objective of this research was to study the efficacy and functionality of ten commercially available WHOs on wrist ROM and grip strength.Design: Randomised comparative functional study of the wrist/hand with and without WHOs.Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 35 publications
(47 reference statements)
4
10
0
Order By: Relevance
“…Two of these, at 18 cm in length (WHO#6 and 10), were the two shortest WHOs tested. This is in line with previous findings where from a biomechanical efficiency perspective, a longer WHO may better control wrist flexion motion (20).…”
Section: Wrist Movement During Each Task Flexionsupporting
confidence: 93%
See 4 more Smart Citations
“…Two of these, at 18 cm in length (WHO#6 and 10), were the two shortest WHOs tested. This is in line with previous findings where from a biomechanical efficiency perspective, a longer WHO may better control wrist flexion motion (20).…”
Section: Wrist Movement During Each Task Flexionsupporting
confidence: 93%
“…These WHOs are 23 cm in length, constructed from a two-way stretch fabric with Velcro® fastenings and an aluminium volar bar. In line with previous research investigating the efficacy of these 10 WHOs in controlling wrist motion, it was concluded that the same WHOs (#1 and 3) performed better in controlling wrist flexion, which was attributed to the improved biomechanical efficiency related to the increased length of these WHOs and the ability to achieve a good fit due to the material of construction (20). In addition, this research has demonstrated that in addition to the aforementioned, the addition of a wrist strap provides enhanced flexion control through activities that require the wrist to be in flexion.…”
Section: Wrist Movement During Each Task Flexionsupporting
confidence: 82%
See 3 more Smart Citations